Pengaruh Manajemen Talenta Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Polowijo Gosari Gresik - Syah, Hubbal Ikmal; Khalikussabir, Khalikussabir; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of talent management and job satisfaction on employee performance at PT. Polowijo Gosari Gresik. The research adopts a quantitative approach with an explanatory research design. The population consists of production employees, with a sample of 70 respondents. The data analysis method used is multiple linear regression.The results indicate that talent management and job satisfaction simultaneously have a significant influence on employee performance. Partially, both variables also show a significant impact on employee performance. The regression model used explains 69.3% of the variance in employee performance, while the remaining 30.7% is explained by other variables outside this study. Keywords: Talent Management, Job Satisfaction and Employee Performance